2006
DOI: 10.1093/treephys/26.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses to water deficit in two Eucalyptus globulus clones with contrasting drought sensitivity

Abstract: We compared the metabolic responses of leaves and roots of two Eucalyptus globulus Labill. clones differing in drought sensitivity to a slowly imposed water deficit. Responses measured included changes in concentrations of soluble and insoluble sugars, proline, total protein and several antioxidant enzymes. In addition to the general decrease in growth caused by water deficit, we observed a decrease in osmotic potential when drought stress became severe. In both clones, the decrease was greater in roots than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 43 publications
8
52
0
4
Order By: Relevance
“…This indicates, up until a certain limit, that the stronger the intensity of the drought, the higher phenotypical variation in response to the stress between specimens of the same family (Ψ a and Ψ 0 ) and between families of P. leiophylla (in the case of Ψ 0 ). This behavior was also observed in E. globulus by Shvaleva et al (2005).…”
Section: Resultados Y Discusiónsupporting
confidence: 75%
“…This indicates, up until a certain limit, that the stronger the intensity of the drought, the higher phenotypical variation in response to the stress between specimens of the same family (Ψ a and Ψ 0 ) and between families of P. leiophylla (in the case of Ψ 0 ). This behavior was also observed in E. globulus by Shvaleva et al (2005).…”
Section: Resultados Y Discusiónsupporting
confidence: 75%
“…On the other hand, proline contribution to osmoregulation is small in most cultivated species under stress conditions [28]. This was also the case with the E. globulus clones under water stress, in which the contribution of this amino acid to the osmotic potential was around 1% [24]. In the present study the lower values of ψ π in leaves under chilling temperatures observed in both clones were not accompanied by proline accumulation either in leaves and roots.…”
supporting
confidence: 69%
“…Pigments were extracted from frozen leaf discs as described in Shvalva et al [24] and then analysed by HPLC according to Wright et al [32] and quantified by custom-made external standard solutions (DHI Water and Environment; Denmark and Carotenature, Switzerland). Twenty-five microliter samples were injected in Zorbax (Agilent Tech., USA) Bonus-RP C18 column and eluted with a quaternary gradient composed of water, acetonitrile, ethyl acetate and 0.5 M ammonium acetate in methanol (20:80, v/v) at flow-rate of 1.0 mL min −1 .…”
Section: Leaf Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from morphological structures contributing to drought stress tolerance, plants have evolved a variety of physiological and biochemical processes, which act as components of drought tolerance , Wang et al 2007. Plants have also developed enzymatic antioxidant systems to cope with drought stress and to avoid oxidative damage (Shvaleva et al 2006, Horváth et al 2007.…”
Section: Introductionmentioning
confidence: 99%